The Satisfaction of Change : How Knowledge and Innovation Overcome Loyalty in Decision-Making Processes /: How Knowledge and Innovation Overcome Loyalty in Decision-Making Processes. (2017) - Del Giudice, Manlio; Della Peruta, Maria Rosaria
No abstract available